Implementasi Pembelajaran Multikultural untuk Meningkatkan Kerukunan Beragama di Sekolah Al–Muwahideen - Yaengkhunchao, Kantatee; Nursyamsiyah, Siti; Putra, Dhian Wahana (Jurnal Pendidikan Islam, 2024)
This research examines the implementation of character education based on multiculturalism at Al-Muwahideen School in Thailand. This qualitative study involves interviews with teachers and students, observations during multicultural education, and the analysis of documents related to student behavior and daily grades. The research results identified four forms of character education implementation at the school, including collective prayer activities, the promotion of universal attitudes among religious communities, the internalization of tolerance values, and the use of lecture and practice methods in teaching. Positive impacts observed include the development of mutual respect among students, the creation of a school climate that promotes learning and tolerance, and the establishment of harmony in the learning process. Supporting factors for multicultural education include the community environment, the curriculum, and facilities, while differences in students' understanding of subjects and their emotional maturity level serve as inhibiting factors.